2018
DOI: 10.1590/1414-431x20187440
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate as a possible disease-modifying osteoarthritis drug: a systematic review

Abstract: Considering that osteoarthritis (OA) is the most prevalent joint disease worldwide, multiple pharmacological treatments have been proposed to alter the articular structure with potential benefit in the progression of the disease. The so-called disease-modifying OA drugs have been frequently investigated but conclusive findings are rare. Strontium ranelate (SrRan) is a drug usually prescribed to treat osteoporosis, with proven effects in decreasing the risk of fractures and possible effect in reducing the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
(71 reference statements)
1
20
0
4
Order By: Relevance
“…It is used for treating osteoporosis and for reducing susceptibility to fractures, while simultaneously enhancing bone density and strength. It overcomes the drawbacks of one-way treatments with other drugs [16]. Many animal experiments have shown that strontium ranelate accelerates the formation of new bone while slowing down the resorption of old bone.…”
Section: Discussionmentioning
confidence: 99%
“…It is used for treating osteoporosis and for reducing susceptibility to fractures, while simultaneously enhancing bone density and strength. It overcomes the drawbacks of one-way treatments with other drugs [16]. Many animal experiments have shown that strontium ranelate accelerates the formation of new bone while slowing down the resorption of old bone.…”
Section: Discussionmentioning
confidence: 99%
“…There was no relationship between taking medications for OA compared with anticoagulants or medicines for diabetes or hypertension. Given that taking medicines (such as strontium ranelate (Rodrigues et al, )) can slow OA disease progression and improve both pain and structural changes (Han et al, ; Wang et al, ), encouraging medicine taking for those at risk of not taking medicines, is clinically warranted. This is further encouraged by the present data, which indicated greater functional performance, as measured by timed chair raises, for individuals who took medications compared with those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Although these have demonstrated moderate to good effect sizes for those who follow this advice, patient experiences surrounding the effectiveness, particularly of paracetamol, have been shown to influence the extent to which pain relief is used (Lee, Cooke, Cooper, & Shield, ). Furthermore, Wang, Xu, Hunter, and Ding () highlighted the importance which some medications, such as strontium ranelate, may offer in respect to symptom improvement and joint structure changes, with a slowing of disease progression (Rodrigues, Freire, Bonfim, Cartágenes, & Garcia, ). Accordingly, encouraging the management of OA symptoms with medicines, particularly in the early stages of the disease, could have longer‐term beneficial consequences (Han, Fan, Bai, & Ding, ).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of osteoblasts is enhanced in the presence of strontium ions, while the activity of the osteoclasts is reduced depending on the concentration of strontium in the microenvironment [ 43 ]. Inhibited activity of osteoclast in the presence of Sr is due to reduced synthesis of matrix metalloproteinase coupled with control of osteoprotegerin-RANKL pathway [ 81 ].…”
Section: Strontium Ranelatementioning
confidence: 99%
“…In clinical usage it was also shown to decrease in patients with primary osteoporosis the risk of vertebral and non-vertebral fractures [ 68 ], femoral bone fractures also being positively impacted [ 63 ]. SrRan remains the main option for cases of severe osteoporosis [ 81 ].…”
Section: Strontium Ranelatementioning
confidence: 99%